2004
DOI: 10.1116/1.1795821
|View full text |Cite
|
Sign up to set email alerts
|

Origin of H− in collisions of hydrogen atoms with an adsorbate-covered Cu(100) surface

Abstract: Results are presented from an experimental study of electron capture and loss during collisions of low-energy hydrogen atoms and ions with a residual gas covered metal surface. Ground-state hydrogen atoms (H1s) and the atomic ions (H−,H+) were scattered from a Cu(100) surface with energies ranging from 25to200eV. Energy loss analysis indicates that the dominant process leading to H− formation proceeds directly through the adsorbed vacuum species, with the metallic crystal acting primarily as a physical scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This indicates that the sample surfaces are kept clean without contamination such as water. 21 On the other hand, for the carbon surface it seems that the H + (H − ) intensity slightly increases (decreases) with increasing temperature. We have confirmed reproducibility of this trend.…”
Section: Figures 3(a)-3(c) Show the Intensities Of The Reflected H +mentioning
confidence: 96%
“…This indicates that the sample surfaces are kept clean without contamination such as water. 21 On the other hand, for the carbon surface it seems that the H + (H − ) intensity slightly increases (decreases) with increasing temperature. We have confirmed reproducibility of this trend.…”
Section: Figures 3(a)-3(c) Show the Intensities Of The Reflected H +mentioning
confidence: 96%
“…Consequently, we expect the charge transfer processes and experimental ion/atom fractions obtained during scattering experiments to be very different for the Cu(100) surface with respect to Cu(111). To the best of our knowledge, there are no experimental data available for H − or H scattering and survival on clean Cu(100). Prior experimental studies reported in the literature include (1) Atomic and ionic hydrogen scattered from Cu(100) covered with a residual gas at very low energy (25 to 200 eV) . This study showed that the dominant process leading to the H − formation proceeds through the adsorbed species, with the Cu(100) surface acting as a scattering platform.…”
Section: Introductionmentioning
confidence: 99%